Genetic Diversity of African Nightshade (Solanum nigrum L.) Complex Accessions from Western Kenya - Mafuta, J. N.; Chepkoech, E.; Onamu, R.; Shibairo, S. I.; Wamocho, L. S. (Africa Environmental Review Journal, 2022)
Kenya. Despite its importance as a nutritious vegetable and having inherent medicinal value, African nightshade has been neglected, few farmers are growing it, there is potential reduction of food supply and these may be as a result of few studies carried out to improve the crop. Recently, growing demand is necessary for the development of improved, high yielding varieties, intensify diversity studies of interest, conservation and utilization of genetic resources especially in Western Kenya. The simple sequence repeats (SSR) technique was used to assess the genetic relationships among 30 african nightshade accessions collected in Bungoma, Kakamega and Trans nzoia counties of Western Kenya. 6 SSR primers were used and each primer generated 1polymorphic band. Polymorphic Information Content ranged from 0.4215 to 0.8212 with a mean of 0.5881. The average heterozygosis’ He=0.9111 for SSR markers used. The dendrogram showed that the accessions grouped into three main clusters showing richness in diversity, it also revealed that the coefficient distance that separated most of the accessions was less than 79.56. These findings show that there were possibilities of cross ability among the accessions, Variation among regions was not genetically evident.